Is There A Monist Theory of Causal and Noncausal Explanations? The Counterfactual Theory of Scientific Explanation. Issue 5 (December 2016) - Reutlinger, Alexander
Abstract : The goal of this paper is to develop a counterfactual theory of explanation (CTE). The CTE provides a monist framework for causal and noncausal explanations, according to which both causal and noncausal explanations are explanatory by virtue of revealing counterfactual dependencies between the explanandum and the explanans. I argue that the CTE is applicable to two paradigmatic examples of noncausal explanations: Euler's explanation and renormalization group explanations of universality.